COVID-19, Influenza and Economic Activity — An Impact Analysis Perspective - Adalbert Winkler (Wirtschaftsdienst)
Abstract The German debate about the policy implications of the coronavirus becomes increasingly heated given different views on the mortality rate from SARS CoV-2, as well as the epidemiological and economic impact of lockdown measures imposed by the government. Impact analysis applying features of randomised control trials would provide clear evidence. However, this is currently unavailable due to a lack of an appropriate control group of countries without measures. Thus, polarisation is likely to rise if observed mortality rates remain low.